Pemanfaatan Media Visual dalam Menunjang Pembelajaran Pendidikan Jasmani di Sekolah Dasar - Maya Jatmika, Herka (Jurnal Pendidikan Jasmani Indonesia, 2005)
Learning tools can help the teachers to teach physical education. Learningtools enable teacher to explore the subject matter and deliver it in a communicativeway. This will make students absorb more and understand the subject or messagefrom teachers.Visual or graphic media is a media related with visualization. This media will assistteachers of physical education. Various visual media that can be use for physicaleducation teachers among others are picture, photo, sketch, chart, cartoon, and poster.The suitable media for elementary school is pictures and photos; nevertheless othergraphic media is also can be use.Before make use of visual or graphic media, physical education teachers has to makeassessment of the learning needs in elementary school and understand well thetechnique and how to use the media.Kata Kunci: Media Visual, Pembelajaran.